Microanatomical Studies on the Lungs in Guinea Pigs - Rajathi, S; Raja, K; Ramesh, Geetha; Kannan, T A; Ushakumary, S (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present work was undertaken with the aim to study the microanatomy of the lungs of six adult healthy guinea pigs. Animals were dissected as per CPCSEA norms and lung pieces were taken. The lungs were cut into small pieces and routine histological tissue processing was done and images were recorded. Histologically lung was covered with visceral pleura and comprised of conductive and respiratory portions. The parenchymatous portions showed bronchi within the lung, tertiary bronchiole and respiratory bronchioles, alveolar duct, and sac which possessed alveoli on its walls. The bronchi were lined with pseudostratified ciliated columnar epithelium. With the bronchi divided from primary to tertiary, the epithelium was changed from respiratory to ciliated simple columnar epithelium with goblet cells. The respiratory bronchioles were lined by cuboidal epithelium without cilia and goblet cells. The alveolar duct, sac and alveoli were lined by simple squamous epithelium. The alveoli contained two types of cells namelytype I pneumocytes and type II pneumocytes. Alveolar macrophages were found.